Building An Automatic Speech Recognition System for Home Automation - Aboulkhir, Mohamed; Khoulji, Samira; Jourani, Reda; Kerkeb, ML (Transactions on Engineering and Computing Sciences, 2017)
This paper presents a study on automatic speech recognition (ASR) systems applied to home automation. So a detailed study of the architecture of speech recognition systems was carried out. The objective is to select a speech recognition software that must operate in remote speech conditions and in a noisy environment. The proposed system is using an ASR toolkit called Kaldi, which must communicate as an open platform communication (OPC) client developed in C++, with any home automation system. The latter behaves like an OPC server.